RUANG TERBUKA DI JAKARTA: ANTARA KENYATAAN DAN HARAPAN - leonardo adi dharma widya (Universitas Andalas, 2014)
The image of the city worse off. Poor transport, congestion, pollution, and flooding becomes a major obstacle. Peace, security, comfort, and the more limited development in Jakarta. This resulted in a decreased quality of life and environment of the city. Basically, the public space is one indicator in determining the Quality of Life in a town populated. However, the design of public spaces often do not refer to the design criteria especially involving people’s aspirations. Discourse of public space often only seen as a purely technical activities and graphics. With the decline in quality of life, resulting in the city often social conflicts, such as racism, rampant: buskers, street children, beggars, begging, vandalism, hooliganism, crime, demonstrations, and student brawls. With the method of qualitative research - Grounded Theory, I would emphasize the discovery of a new theory which is based on the results of empirical observation data, inductive, generative nature and the data as evidensi, to review the condition of the open space in Jakarta. With the results of exposure to the new theory conceptualization embodies the ideal of public space that should be realized, to bridge the expectations/desires of the population of Jakarta and is intended to provide input for the study of public spaces Jakarta in particular, as well as food for thought for local development in general